Penerapan Cobit 5 dalam Evaluasi Tata Kelola Teknologi Informasi (Studi Kasus: Dinas Perindustrian dan Perdagangan Provinsi Sumatera Utara) - Muhammad Dedi Irawan; Alya Seraya; Novita Amalia; Reza Rizki Arifianda (Program Studi Teknik Informatika Universitas Pamulang, 2020)
The Department of Industri and Trade of North Sumatra Province is part of the government in the industrial and trade sector. In carrying out its operational activities, the use of information technology is used to support activities. Some problems that occur are the absence of a system for evaluating information technology governance that is used in a systematic manner. In examining the technology used, it only involves a few expert reasoning skills. The purpose of this study is to determine the extent of management and utilization of information technology in the Department of Industri and Trade of North Sumatra Province and to recommend information technology management policy proposals using COBIT version 5. The process of evaluating governance using COBIT begins with domain selection, primary and secondary data koleksi. , the mapping process, the next step is to process the questionnaire data and calculate the value and level of capability. The results of the application of COBIT 5 can explain the situation in resource optimization which includes planning, pengawasan, and adjustments to the implementation of processes and conditions that have not been met, such as making documentation regarding the management of relationships between business and information technology, making SOPs containing regulating coordination.